The Effect Of Giving Carrot Juice On Menstrual Pain In Young Women - Aida Fitria; Marisa Marisa (Science Midwifery, 2022)
Menstrual pain (dysmenorrhea) is a lower abdominal pain that usually occurs in women who have menstruation which has a bad effect and causes disturbances to carry out daily activities because of the pain they feel. This condition can last for two days or more than the length of menstruation experienced every month. Objective to reduce menstrual pain, you can use nonpharmacological therapy, one of which is carrot juice. This study aims to determine the effect of carrot juice minun on reducing menstrual pain in young women at SMA Negeri 9 Medan. This research is a quantitative research using a pre-experimental design with a one group pre-post test approach. The population in this study amounted to 40 people. The data were collected using an observation sheet on the menstrual pain scale (dysmenorrhea) before and after being given carrot juice. The sample of this study was a student of SMA Negeri 9 Medan which was obtained through accidental sampling, which was 9 people. Data analysis using the Wilcoxon test. The results of the study showed differences in the average value of decreasing menstrual pain before and after being given carrot juice, from 2.67 to 1.22. The results of stascal tests with Wilcoxon test results obtained an A–Symp Sig (2-tailed) value of p= 0.006 (< 0.05). There is an influence of drinking carrot juice on the decrease in menstrual pain. It is recommended for respondents to consume carrot juice during menstruation as a non-pharmacological therapeutic therapy by drinking carrot juice juice 2 times a day as much as 400 ml, namely 200 ml in the morning and 200 ml in the day at the time of mesntruation on the first day.